Boron-Doped Pine-Cone Carbon With 3D Interconnected Porosity for Use as an Anode for Potassium-Ion Batteries With Long Life Cycle - Lu, Jian-Fang; Li, Ke-Chun; Lv, Xiao-Yan; Kuai, Hong-Xiang; Su, Jing; Wen, Yan-Xuan (Frontiers in Chemistry, 2022)
Potassium-ion batteries (KIBs) have received widespread attention as an alternative to lithium-ion batteries because of their low cost and abundance of potassium. However, the large radius of potassium results in poor kinetic performance and the electrode experiences severe volume changes during charging/discharging, resulting in low capacity and rapid decay. Therefore, the development of anode materials with sufficient space and active sites for potassium ion deintercalation and desorption s necessary to ensure structural stability and good electrochemical activity. In this study, boron-doped pine-cone carbon (BZPC) was prepared in ZnCl2 molten-salt by calcination under high temperature. The 3D interconnected hierarchical porous structure formed by the synergistic effect of B-doping and ZnCl2 molten-salt promoted the penetration of the electrolyte, improved charge-carrier diffusion, alleviated volume changes during cycling, and increased the number of micropores available for adsorbing potassium ions. In addition, due to B doping, the BZPC material possessed abundant defects and active centres, and a wide interlayer distance, which enhanced the adsorption of K ions and promoted their intercalation and diffusion. When used as the anode of a KIB, BZPC provided a high reversible capacity (223.8 mAh∙g-1 at 50 mA∙g-1), excellent rate performance, and cycling stability (115.9 mAh∙g-1 after 2000 cycles at 1 A∙g-1).